Enclose | Build : Walls, Facade, Roof - Wartzeck, Susanne; Herrmann, Eva Maria; Krammer, Martin; Sturm, Jörg (Scale, 2015)
The fifth volume of the SCALE series is an indispensable tool for every architect and planner. It shows the conditions under which certain constructions can be employed and why; what criteria can influence the choice of a system. The book also offers a look at future developments. How will the facade evolve as an interface for information? What do viable concepts for environmentally active, energy-efficient building shells look like?